Sports coaches` mentorship: experience and a suggested future framework - Bailey, J.; Jones, R. L.; Allison , W. (European Journal of Human Movement, 2019)
Introduction: Mentoring is widely advocated as an important component of coach learning, both informally and as a constituent feature of coach development programmes. However, despite its ubiquity, there remains a paucity of empirical evidence to support mentoring`s use in practice. Consequently, the purpose of this paper is to present an empirical case study of a formalised mentoring programme as experienced by the mentors, and to contribute towards a critical conceptualisation of mentoring in sports coaching. Materials and methods: Eight mentors participated in the study, all being employed on a formalised mentoring programme. Data collection occurred over the 18-month duration of the programme to respect the longitudinal nature of the mentoring process. The data were analysed thematically. Results: The results emphasised the need for a clearer conceptualisation of mentoring to successfully operationalise practice. Although the relational aspect of the role was deemed crucial, developing reciprocity was challenging. This was because of the limited shared or critical understanding of the role among the participants. Discussion: Building on the portrayal of mentoring depicted in the results, we subsequently position mentoring as a relational and contextualized activity. In doing so, we claim a more realistic, coherent and effective pedagogy of mentoring.